Late Complications and Sequelae in Patients after Congenital Heart Disease Operation - Tanitame , Nobuko; Tani , Chihiro; Tachikake , Toshihiro; Tamura , Akihisa; Hieda , Masashi; Urashima , Masaki (Seram, 2021)
【Objective】Life prognosis of patients with congenital heart diseases (CHD) has markedly improved with recent advances in surgical procedures, perioperative management, and subsequent medical treatment. As, at present, large numbers of postoperative CHD patients are long-term survivors, radiologists often encounter the images of these patients. There are various circulation states of postoperative CHD patients. With longer postoperative periods, more complications and sequelae due to long-term hemodynamic changes occur. In particular, in patients after Fontan surgery, hemodynamics due to single ventricular circulation is unique, and late complications are major problems (so-called post-Fontan syndrome). This education exhibit presents some late complications and sequelae in postoperative CHD patients.【Materials and Methods】We demonstrate various image findings of complications and sequelae in long-term followed-up postoperative CHD patients (by X-ray, CT, MRI, angiogram, and RI) and consider which of these can serve as helpful information and suggestions for clinicians.【Results】Contents of this exhibition: cardiac enlargement, some abnormalities associated with congestion (liver dysfunction, protein-losing enteropathy, and plastic bronchitis), collateral formations (pulmonary arteriovenous malformation and veno-venous shunts), cerebral infarction, intestinal ischemia, embolism, hemorrhagic complications, organ atrophy, cholelithiasis, abscess formation, obstruction or deformation of a cardiac conduit, blood flow imbalance, and so on.【Conclusion】We presented image findings of late complications and sequelae in postoperative CHD patients. We think that this knowledge is important to clinical radiologists.